LAJU PERTUMBUHAN SPESIFIK DAN TOTAL LIPID CHAETOCEROS CALCITRANS YANG DI INJEKSI DENGAN KONSENTRASI CO2 YANG BERBEDA - Turnip, Gilbert; Nomleni, Aryok; Adin, Lutfi (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2022)
The microalgae Chaetoceros calcitrans can photosynthesize and grow rapidly. Carbon dioxide (CO2) is very important role in the process of photosynthesis. CO2 injection is required for use in photosynthesis, so it is expected to increase the specific growth rate and reduce greenhouse gases. This research was conducted using experimental laboratory methods, using 4 treatments, namely CO2 injection with concentrations of 10%, 20%, 30%, 40% and without CO2 injection (control) with 4 times variations. The highest specific growth rate occurred on the second day, namely the 10%, 20%, 30%, 40% and control treatments, respectively 0.90, 0.81, 0.78, 0.86 and 0.81 with a doubling time of 0, 77, 0.86, 0.89, 0.81 and 0.85. The highest total lipid obtained with the addition of 10% CO2 was 52.69 (dry weight) while the lowest was the control treatment (ambient air) which was 23.37 ( % dry weight), although the lipid results obtained were not directly proportional to the CO2 concentration and based on the ANOVA test followed by the 5% BNT test did not show a significant difference (p<0.05).